2011
DOI: 10.1073/pnas.1103353108
|View full text |Cite
|
Sign up to set email alerts
|

Soils on exposed Sunda Shelf shaped biogeographic patterns in the equatorial forests of Southeast Asia

Abstract: The marked biogeographic difference between western (Malay Peninsula and Sumatra) and eastern (Borneo) Sundaland is surprising given the long time that these areas have formed a single landmass. A dispersal barrier in the form of a dry savanna corridor during glacial maxima has been proposed to explain this disparity. However, the short duration of these dry savanna conditions make it an unlikely sole cause for the biogeographic pattern. An additional explanation might be related to the coarse sandy soils of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 34 publications
0
58
1
Order By: Relevance
“…2). Most areas with high predicted Dipterocarp richness correspond with the localities that were characterized as Dipterocarp forest by Slik and colleagues (21), with the exception of Bangka island, which is known for tin mining and is characterized by large areas of ultramafic (toxic to many species) and nutrient-poor sandy soils that, in reality, support low levels of Dipterocarp richness. SDM predictions for all of Sundaland show that central Sundaland could harbor another area of high Dipterocarp richness, if it were completely exposed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Most areas with high predicted Dipterocarp richness correspond with the localities that were characterized as Dipterocarp forest by Slik and colleagues (21), with the exception of Bangka island, which is known for tin mining and is characterized by large areas of ultramafic (toxic to many species) and nutrient-poor sandy soils that, in reality, support low levels of Dipterocarp richness. SDM predictions for all of Sundaland show that central Sundaland could harbor another area of high Dipterocarp richness, if it were completely exposed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Slik and colleagues (21) showed that genera with distributions spanning Sundaland from Borneo to Sumatra had a higher tolerance for sandy soils. The few existing maps of the seafloor of the Java Sea indeed indicate the presence of sections with sand ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This rather decisive break contrasts strongly with the situation in western Sundaland, where the Sumatran, Malayan, and Bornean populations have extensively interbred, presumably during a series of glacial events, including the last glacial maximum . We may also assume, with some confidence, that the Natuna Islands' population of Rufous-tailed Tailorbird interbred with Bornean and other western populations during the late Quaternary because of the Natunas' intervening position (Figure 1) and the likely paleodistributions of appropriate coastal habitats (Voris 2000, Cannon et al 2009, Slik et al 2011. The situation for the Rufous-tailed Tailorbird populations of Cagayan Sulu and the Sulu Archipelago east of Borneo, however, remains unclear, as we have not compared (the rare) specimens from these islands and are uncertain about the extent and timing of the islands' connections to Borneo or (in the case of Cagayan Sulu) to Palawan.…”
Section: Biogeographic Patternsmentioning
confidence: 99%
“…We now know, however, that invasions of the Philippines by many Asian forest animals occurred much earlier than the late Pleistocene, and the route through Palawan was less important than previously believed (e.g., for birds: Lim et al 2010, Sheldon et al 2012, Gamauf and Haring 2004, Moyle et al 2007, Jones and Kennedy 2008, Sheldon et al 2009). The Sunda shelf, when exposed as land, does not simply transform into a wide expanse of rainforest through which forest animals can easily travel, but rather it seems to become a matrix of diverse habitats and montane and river barriers (Brandon-Jones 1998, Gathorne-Hardy et al 2002, Meijaard and van der Zon 2003, Gorog et al 2004, Cannon et al 2009, Wurster et al 2010, Slik et al 2011. Movement though Palawan is further impeded by water barriers at both ends, making it act more as a filter or cul-de-sac than a transmigration facilitator (Esselstyn et al 2010).…”
Section: Introductionmentioning
confidence: 99%